2007
DOI: 10.1007/s00125-007-0735-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac contractile dysfunction in insulin-resistant rats fed a high-fat diet is associated with elevated CD36-mediated fatty acid uptake and esterification

Abstract: Aims/hypothesis Changes in cardiac substrate utilisation leading to altered energy metabolism may underlie the development of diabetic cardiomyopathy. We studied cardiomyocyte substrate uptake and utilisation and the role of the fatty acid translocase CD36 in relation to in vivo cardiac function in rats fed a high-fat diet (HFD). Methods Rats were exposed to an HFD or a low-fat diet (LFD). In vivo cardiac function was monitored by echocardiography. Substrate uptake and utilisation were determined in isolated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
177
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(197 citation statements)
references
References 45 publications
(79 reference statements)
10
177
3
Order By: Relevance
“…Furthermore, it is suggested that inflammatory signals produced by EF, associated with low levels of adiponectin, may increase the membrane localization of CD36 in cardiomyocytes and consequently increase myocardial lipid uptake. 49 Cardiac adiposity and heart function in obesity B Gaborit et al EFV and MTGC are related to each other, but do not accumulate in a similar way. The molecular characteristics of EF are perhaps as important as EFV.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is suggested that inflammatory signals produced by EF, associated with low levels of adiponectin, may increase the membrane localization of CD36 in cardiomyocytes and consequently increase myocardial lipid uptake. 49 Cardiac adiposity and heart function in obesity B Gaborit et al EFV and MTGC are related to each other, but do not accumulate in a similar way. The molecular characteristics of EF are perhaps as important as EFV.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of cardiac dysfunction following Western diets is more rapid in Wistar rats, in which high-fat feeding for 7 weeks leads to myocardial steatosis, impaired contractile function and mitochondrial degeneration. Myocardial fatty acid uptake is increased in Wistar rats fed on a Western diet owing to increased sarcolemmal CD36 (Ouwens et al, 2005;Ouwens et al, 2007). Substrate oxidation and myocardial oxygen consumption have not yet been evaluated in this model.…”
Section: Disease Models and Mechanisms Dmmmentioning
confidence: 99%
“…High fat feeding induced insulin resistance in C57BL/6 mice also causes cardiac remodelling and systolic dysfunction [202]. The authors and other research groups have however also shown that rodent models of diet-induced obesity with insulin resistance have either normal [90,203,205,209,210] or compromised [110,203,204,211,212] cardiac mechanical function. It is currently not possible to conclusively attribute the cardiac dysfunction reported in these studies to myocardial insulin resistance since there are several studies that have reported normal cardiac function in animal models with insulin resistance [90,203,205,209,210].…”
Section: Effect Of Insulin Resistance On Cardiac Mechanical Functionmentioning
confidence: 95%